STAKEHOLDERS’ PERCEPTION OF UNIVERSAL BASIC EDUCATION IN KADUNA AND PLATEAU STATES - Bahago, Beatrice Ahmadu (Sokoto Educational Review, 2011)
The study looked into the perception of stakeholders on the implementation of Universal Basic Education for sustainable development. Five research questions were raised during the course of the study. The population consists o f 1000 stakeholders (30 SUPEB staff, 250 teachers, 360 students and parents) participated in the study. A reliability coefficient of 0.77 of Cronbach Alpha was determined. Descriptive statistics comprising percentages mean and standard deviation was used fo r data analysis. Findings revealed that though there is remarkable difference between UBE and UPE, funding was inadequate. Teachers’in terms o f quantity and quality are not adequate. UBE impact on sustainability is being threatened by incessant strikes due to lack o f job satisfaction by teachers. It was therefore recommended that improved fin d in g be made to enhance prompt payment o f staff salaries